Família e educação em folders de bancos: questões para o currículo escolar - Jesus, Luciane Helena Ferreira de (Universidade do Vale do Rio do Sinos, 2007)
Taking as a reference the field of Cultural Studies in a post-structuralist perspective and approaching the thoughts of Foucault with this dissertation Family and Education in Bank Brochures: questions for the school curriculum, I try to analyze how the speeches in Bank Brochures draw the family’s attention so that they feel seduced to purchase the products there advertised to invest in their own “safety” and in their children’s education. Going through bank brochures I see them as a cultural artifact which takes the place of a Cultural Pedagogy since they teach those who read them to act in a certain way judged as the most adequate to live in a society stained by insecurity and instability. Keen to find wording concerning family and education I took 10 out of 93 brochures to make up the corpus of analysis. Handling them to study how their contents place family towards education producing truths about school and education I started making my point on the relations found. These wordings on the whole allowed me
Keywords: currículo escolar; discurso educacional; folders de bancos; pedagogia cultural; família; cultural pedagogy; brochures of banks; school curriculum; family; Ciências Humanas